Removal of Chromium (VI) from Aqueous Solution using Charred Pomegranate Waste - Gautam, Rajendra Prasad; Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2013)
Removal of Cr(VI) from aqueous solution was studied using charred pomegranate fruit waste [CPW] as a new low cost biosorbent under batch method at room temperature. Its efficiency for removal of Cr(VI) was compared with raw pomegranate fruit waste[RPW]. Various sorption parameters such as contact time, initial concentration of Cr(VI) ion and effect of pH on the adsorption capacity of the biosorbent were studied. The adsorbent was effective for quantitative removal of Cr(VI) ions in highly acidic condition (pH=1) and equilibrium has been achieved in 2 hours. The adsorption isotherm data were fitted to Langmuir and Freundlich adsorption isotherm models and the model parameters were evaluated. Spectrophotometric method using diphenylcarbazide as a complexing reagent was used to analyze the chromium content in synthetic samples and the landfill site effluent collected from Kuleshwor, Kathmandu, Nepal. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9256 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 81-88 Uploaded date: 12/5/2013